Peran DPRD dalam Pengawasan Implementasi Program Pembangunan Infrastruktur Jalan di Kabupaten Bintan - Irma Lusiyana; Rahayu Septia Lestari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of the Regional People's Representative Council (DPRD) in supervising the implementation of road infrastructure development programs in Bintan Regency. Using a qualitative approach based on literature studies, this study examines how the DPRD carries out its supervisory function to ensure transparency, efficiency, and accountability in the implementation of infrastructure projects. The results of the study show that although the DPRD has a constitutional mandate to carry out supervision, its implementation still faces various challenges. These challenges include limited competent human resources, weak political will to follow up on supervisory findings, and suboptimal coordination between the executive and the legislature. This condition has an impact on the effectiveness of supervision and the quality of infrastructure development that has not fully met the principles of good governance. This research emphasizes the importance of increasing the institutional capacity of the DPRD through training, strengthening regulations, and utilizing information technology. In addition, public participation in the supervision process also needs to be increased as a form of constructive social control. Thus, the DPRD's supervision of infrastructure development can run more effectively and contribute to the creation of sustainable, transparent, and accountable regional development.